A SOCIOLINGUISTICS FEATURE OF ADDRESS FORMS IN MALAY BENGKULU - Meylina Meylina (UNIVED Press, 2014)
This paper explored various forms of address in Bengkulu which may help in understanding the culture of the people and also in knowing the reason why the people behave the way they do in an encounter with others in different situations. The address terms examined in this paper are limited to names only. Pronouns and other forms were not included. The study entails an approach namely collection of data by means of questionnaire and introspection by native speakers from within their own circle of friends and relations in both nuclear and extended family. Twenty participants assisted in collecting the various forms of Bengkulu address terms from their friends and relations by means of audio-recording and notes of people's address behavior. The findings showed that the titles vary from those derived from kinship terms, chieftaincy, age, and social as well as distance of the people. Address forms such as last name is rarely used. Indeed, first names are often used when addressing a person who is junior or to show intimacy among them. At last, this study also found that the address term teknonym appears to be a infrequently feature of address in Malay Bengkulu. Keywords: Address forms, culture, titles, first name, last name.